2020
DOI: 10.1101/2020.05.29.20116376
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early transmission of SARS-CoV-2 in South Africa: An epidemiological and phylogenetic report

Abstract: Background: The emergence of a novel coronavirus, SARS-CoV-2, in December 2019, progressed to become a world pandemic in a few months and reached South Africa at the beginning of March. To investigate introduction and understand the early transmission dynamics of the virus, we formed the South African Network for Genomics Surveillance of COVID (SANGS_COVID), a network of ten government and university laboratories. Here, we present the first results of this effort, which is a molecular epidemiological study of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…As of July 21, SARS-CoV-2 has spread to 188 countries with around 14 763 911 confirmed cases and 611 322 fatalities 9 . To characterize SARS-CoV-2 local transmission across the globe 10 , the few mutations accumulated to date in the viral genome [11][12][13] have allowed the characterization of different lineages or clades (A and B) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…As of July 21, SARS-CoV-2 has spread to 188 countries with around 14 763 911 confirmed cases and 611 322 fatalities 9 . To characterize SARS-CoV-2 local transmission across the globe 10 , the few mutations accumulated to date in the viral genome [11][12][13] have allowed the characterization of different lineages or clades (A and B) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we conducted a comprehensive literature search for publications on community-based epidemiological studies of SARS-Cov2 in developing countries (using relevant keywords), and identified no high-quality published population-based study assessing the incidence of SARS-CoV-2 infection in community-based settings in developing countries. We only found four preprints on serological surveys in Iran, South Africa and Brazil, all taking probabilistic samples in small fractions of the studied populations [20,21,22,23]. However, the design of those studies does not allow to ascertain the incidence of this infection.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, only limited sequencing data of Northern Africa and the Sahel region is available compared to other regions of the world like America, Asia or Europe. Viral genomes spreading on the African continent are mainly accessible from states like South Africa [24], the Democratic Republic of Congo (DRC) and Kenya [25]. For the Sahel region, genomic information of SARS-CoV-2 is only provided by Nigeria [26] and Senegal [5,27], while data from countries like Mauritania, Niger, Burkina Faso, Chad, Eritrea and Sudan is still missing.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the B.1 lineage comprises sequences associated with the large Italian outbreak in February 2020 and represents to date (date 21.07.2020), together with its sublineage B.1.1, the worldwide prevalent virus clade [19]. The African continent, especially South Africa is dominated by lineage B (its origin still lying in Asia) and B.1 [24]. In Mali, only ⅓ of the patient samples were assigned to lineage B.1, thus giving rise to speculation that this and Sahelian G5 partner countries.…”
Section: Discussionmentioning
confidence: 99%